Association of Serum Bilirubin Levels with Macro- and Microvascular Complications in Chinese People with Type 2 Diabetes Mellitus: New Insight on Gender Differences - Li S; Li N; Li L; Wang Y; Liu Y; Wang Y; Zhan J (Diabetes, Metabolic Syndrome and Obesity, 2023)
Shuang Li, Niman Li, Linsen Li, Yi Wang, Youshuo Liu, Yanjiao Wang, Junkun Zhan Department of Geriatrics, the Second Xiangya Hospital, Institute of Aging and Age-Related Disease Research, Central South University, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Yanjiao Wang; Junkun Zhan, Department of Geriatrics, the Second Xiangya Hospital, Institute of Aging and Age-Related Disease Research, Central South University, Changsha, Hunan, People’s Republic of China, Email ls330013@163.com; zhanjunkun@csu.edu.cnBackground: Previous studies suggested protective effects of bilirubin against cardiovascular disease, with a possible gender difference. However, the relationship between serum total bilirubin (TBIL) with diabetic macro- and microvascular complications remains unknown. We aimed to examine the association of macro- and microvascular complications with serum TBIL levels.Methods: Serum TBIL was measured in 648 patients with T2DM. Demographic and clinical data were obtained from the inpatient medical record system. Serum TBIL was measured with an automatic biochemistry analyzer according to routine protocols. Parameters of vascular complications, including ankle-brachial index, carotid intima-media thickness, estimated glomerular filtration rate and the urinary albumin to creatinine ratio, were measured and calculated. The association between TBIL and diabetic macro- and microvascular complications was analyzed.Results: In multivariable logistic regression, after adjustment for age, sex, body mass index and diabetic duration, higher serum TBIL levels were significantly associated with decreased odds of microalbuminuria (OR = 0.31, [95% CI] 0.16– 0.61, P = 0.003) and chronic kidney disease (OR = 0.19, [95% CI] 0.09– 0.41, P < 0.001). These associations were only found in male but not in female patients. However, no significant relationship was found between TBIL and peripheral arterial disease or carotid hypertrophy.Conclusion: Our findings suggest that physiological higher TBIL level might be a protective factor for diabetic microvascular complications.Keywords: total bilirubin, diabetic macrovascular complications, diabetic microvascular complications, gender difference